Knowledge, Attitude and Practice regarding Iodine Deficiency Disorder among Pregnant Women at Srinagarind Hospital, Khon Kaen, Thailand - Jitsupa Khamsingnork; Chompilas Chongsomchai; Chusri Kuchaisit; Pisake Lumbiganon (Thai Journal of Obstetrics and Gynaecology, 2016)
Objectives: This study assessed the knowledge, attitude, and practice regarding iodine deficiency disorder (IDD) and supplementation among pregnant women at Srinagarind Hospital, Khon Kaen University, Thailand. Materials and Methods:We performed a cross sectional study. A total of 363 first antenatal-visit pregnant women at Srinagarind Hospital, Khon Kaen University during October 2014 to April 2015 were included. Data was collected using self-administered semi-structured questionnaire and interview. Descriptive analysis was conducted and univariate and multiple logistic regression analyses were used to identify factors associated with practice regarding IDD.Results: Among 363 pregnant women, only 121 (33.33%) participants had good knowledge, only 128 (35.26%) participants had good attitude regarding iodine deficiency, and only 86 (23.69%) participants reported good practice of iodine supplementation. There were 309 (85.12%) pregnant women received information regarding IDD. Pregnant women with good knowledge of IDD had significantly better practice (AOR = 2.34, 95% CI 1.09, 5.01). Women with good attitude toward IDD had significantly better practice (AOR = 5.41, 95% CI 1.53, 19.05). Also, receiving IDD information significantly associated with good practice (AOR = 5.61, 95% CI 1.29, 24.29).Conclusion: Knowledge, attitude, and practices regarding IDD and supplementation among pregnant women were insufficient. Healthcare providers at all levels should put more intensive effort in addressing this very important health problem.